Recent progress of geopolymers for carbon dioxide capture, storage and conversion - Sk S. Hossain; Farid Akhtar (Journal of CO2 Utilization, 2023)
Geopolymer materials have garnered considerable interest as one of the most promising eco-friendly inorganic options over the last decade, thanks to their remarkable properties, including mechanical, chemical, and thermal stability, cost-effectiveness, and sustainable synthesis process, enabling their use in numerous high-value applications. Meanwhile, the ever-increasing concentration of CO2 in the atmosphere is an urgent concern for the environment and human health, forcing the development of effective CO2 capture, storage, and transformation strategies. Various potential solutions for reducing carbon emissions have emerged with the advancement of novel materials and technologies for CO2 capture from exhaust streams and air. Concurrently, significant studies have been conducted on utilizing geopolymers as a sustainable material for CO2 capture. This review provides a comprehensive overview of geopolymers' recent advances and obstacles for CO2 management. We focus on state-of-the-art geopolymer foams and their composites, highlighting their potential for capturing CO2. In addition, we review the use of geopolymers as catalysts or precursors for converting CO2 into value-added chemicals and their potential for geological CO2 sequestration. Moreover, we analyze the current limitations and opportunities for further development of geopolymers in CO2 management. The review provides a perspective on the role of geopolymers in mitigating CO2 effects on the environment and advancing a sustainable future.